1985
DOI: 10.1093/jn/115.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Rat Pancreatic β-Cells in Protein Deficiency: A Study Involving Morphometric Analysis and Alloxan Effect

Abstract: The possible cause(s) of impaired glucose tolerance in protein-calorie malnutrition was studied. The beta-cell mass was morphometrically determined and the sensitivity to alloxan was characterized in rats fed ad libitum a 4% protein diet, pair-fed or fed ad libitum a 20% protein diet. The percentage of beta-cells in the pancreas was neither affected by protein deficiency nor influenced by caloric intake. However, the diabetogenicity of alloxan was greatly reduced in protein-malnourished rats. This reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
2
12
0
3
Order By: Relevance
“…In the same experimental rat model we have previously reported that the in vivo insulin response to glucose was very poor [5] in agreement with previous reports in similar models [3,15,17,18], and that this impairment of insulin release was related at least in part to intrinsic abnormality(ies) of the pancreatic betacells [5,17]. It is also notable that in the same rat model, protein-energy malnutrition has been reported to cause a diminution of beta-cell mass [19] and that such beta-cell atrophy is a feature rather typical of protein shortage [19][20][21][22]. Under basal postabsorptive conditions and in the face of drastically lowered plasma insulin levels, protein-energy restricted rats maintained low basal plasma glucose levels.…”
Section: Discussionsupporting
confidence: 88%
“…In the same experimental rat model we have previously reported that the in vivo insulin response to glucose was very poor [5] in agreement with previous reports in similar models [3,15,17,18], and that this impairment of insulin release was related at least in part to intrinsic abnormality(ies) of the pancreatic betacells [5,17]. It is also notable that in the same rat model, protein-energy malnutrition has been reported to cause a diminution of beta-cell mass [19] and that such beta-cell atrophy is a feature rather typical of protein shortage [19][20][21][22]. Under basal postabsorptive conditions and in the face of drastically lowered plasma insulin levels, protein-energy restricted rats maintained low basal plasma glucose levels.…”
Section: Discussionsupporting
confidence: 88%
“…They also observed a decrease in the number of large islets, in the islet diameter, and in endocrine volume when compared to controls. Similar ly, after the same treatment, Dixit and Kaung [1985] came to the same conclusion. Furthermore, the results of de Gasparo et al [1978] highlight the role of the amino acids for the proliferation of the fetal B cells.…”
Section: Discussionsupporting
confidence: 57%
“…A control group of virgin female Wistar rats re ceived a diet containing 20% protein [Weinkove et al, 1977;Dixit and Kaung, 1985;Rodrigues et al, 1985), and a LP group received an isocaloric diet con taining 8% protein (table 1). The females were caged with males overnight and coitus was determined by inspection of vaginal smears; y 0 of gestation being the first day after coitus.…”
Section: Methodsmentioning
confidence: 99%
“…Although attenuation of islet size/volume with low-protein feeding has previously been reported in lean rats (3,13,21,29), this is the first study to report similar changes in P-cell mass in obese rats fed low protein. The attenuation of islet sizeholume with protein deficiency might be related to a decrease in islet proliferation.…”
Section: Discussionmentioning
confidence: 42%